Therapeutic Effects of Olive Oil in Diabetic Rat - Fahad, Omar Attalla (International Journal of Psychosocial Rehabilitation, 2020)
The current study conducted for evaluation the therapeutic effects on diabetic rats. Forty male rats were used in this study which divided into 4 groups, 10 rats were in each group, Group A serve as control group, Group B given alloxan monohydrate at dose of (150 mg/ kg), Group C given alloxan monohydrate at dose of (150 mg/ kg) then received orally (0.5 ml/kg B.W) of olive oil for 4 weeks, Group D received orally (0.5 ml/kg B.W) of olive oil for 4 weeks (control positive). blood samples were aspirated at zero, 15 and 30 days of experiment to estimate the blood glucose, cholesterol and HDL. Pancreas and liver were taken for histopathology. The results showed an increase in blood glucose, cholesterol in group B and decreasing in HDL levels. Group C showed significant (P<0.05) decreased in serum glucose and cholesterol concentration at days 15 and 30 compared with Group A and D, while the HDL showed significant increase as compared with control group. Group D showed only significant increase in HDL concentration. Histopathology of pancreas showed in group B at all period showed no difference in histopathological changes, which characterized by moderate atrophy with reduced number of islet cells to severe atrophy ,shrunken in size, severe destruction of the islets of Langerhans. Islet cells showed vaculations. Also, liver of Group B showed severe fatty change with acute cellular degeneration with congestion of sinosoides with inflammatory cell infiltration mostly lymphocytic cuffing, while pancreas of treated rats with olive oil at day 30 showed mild to moderate reduction in the size and number of the islets in this group. In Group C, the liver architecture appears more or less like control group with the exception of some congestion areas in the blood sinusoids. In conclusion, Olive oil can alleviate the adverse effects of diabetes in rats.